[tex] A=\left[\begin{array}{cc}2&-2\\1&-1\end{array}\right]
\\ \det(A)=2\cdot (-1) -(-2)\cdot1=0\\
A^2=\left[\begin{array}{cc}2&-2\\1&-1\end{array}\right]\left[\begin{array}{cc}2&-2\\1&-1\end{array}\right]=\left[\begin{array}{cc}2&-2\\1&-1\end{array}\right].\\
\text{de unde } p=1.\\
A+B=\left[\begin{array}{cc}2&-2\\1&-1\end{array}\right]+\left[\begin{array}{cc}0&b\\b&0\end{array}\right]=\left[\begin{array}{cc}2&b-2\\1+b&-1\end{array}\right]\\
\det(A+B)=2\cdot(-1)-(b-2)(1+b)=0\\
\Rightarrow b=0 \vee b=1[/tex]